THE EFFECT OF CR2O3 ON THE PARTIAL MELTING OF SPINEL LHERZOLITE IN THE SYSTEM CAO-MGO-AL2O3-SIO2-CR2O3 AT 1.1 GPA - Liu Xi.; Oneill H.St.C. (My University, 2004)
Chromium as Cr3+ substitutes for octahedrally coordinated Al in upper-mantle minerals, thereby reducing the activity of Al2O3 in the system and hence the concentration of Al2O3 in partial melts. The effect of Cr2O3 on melt compositions multiply saturated with the spinel lherzolite phase assemblage has been quantified in the system CaO–MgO–Al2O3–SiO2–Cr2O3 at 1·1?GPa as a function of 100 Cr/(Cr + Al) in the spinel (Cr#sp). The decrease of Al2O3 in the melt with increasing Cr#sp is accompanied by increasing MgO and SiO2, whereas CaO remains almost constant. Consequently, the CaO/Al2O3 ratio of the melt increases with Cr#sp, and the melt becomes richer in normative diopside, hypersthene and quartz. The effect may explain certain mantle melts with unusually high CaO/Al2O3 ratios. The concentration of Cr2O3 in the melt remains low even at high Cr#sp, which means that the strong effect of Cr2O3 on partial melting equilibria is not readily apparent from its concentration in the melt itself. The existence of a highly refractory major component such as Cr2O3 ifies simplified conclusions from the ‘inverse approach’ in the experimental study of basalt petrogenesis, as there is insufficient information in the composition of the partial melt to reconstruct the conditions of melting.
Keywords: basalt petrogenesis; partial melting; reversal experiment; spinel lherzolite; system CMAS–Cr2O3; CaO/Al2O3 of melt; effect of Cr2O3